(untitled) (JS (JURNAL SEKOLAH), 2021)
Abstract: The Effectiveness of the Google Form Assisted Pretest Method on Student Learning Outcomes with the Theme of Always Saving Energy Class IV SDN Sriwedari 01. This research was conducted due to the low learning outcomes of fourth grade elementary school students in learning during the Covid-19 pandemic. While the low learning outcomes of students, caused by the low learning outcomes are the lack of effective learning in optimizing the learning outcomes of fourth grade students during the Covid-19 pandemic. Therefore, this study aims to determine the effectiveness of the Google Form-assisted pretest method on the learning outcomes of students with the theme Always Save Energy for class IV SDN Sriwedari 01. This research was also conducted using quantitative research methods with the type of research being true experimental design and the static group comparison design. The population used were fourth grade students at SDN Sukorukun as a control class and fourth grade students at SDN Sukorukun as an experimental class for the 2020/2021 school year, with a total sample of 37 students consisting of 21 control class students and 16 students in the control class. experiments using non-probably sampling technique. The data taken in this study were through interviews, questionnaires/tests, documentation, and observation. Student learning outcomes from the questionnaire/test data show that the percentage of classical completeness in the experimental class (68,75%) is smaller than the percentage of classical completeness in the control class (90,48%) with the KKM value of the control class and experimental class, which is 65. While in the analysis t-test, obtained tcount = 0,55 and ttable = 2,08 so that the obtained tcount < ttable with the difference in the percentage of classical completeness of students who complete the KKM of 21,73%. So that the Google Form-assisted pretest method is not effective on the learning outcomes of students with the theme Always Save Energy for class IV SDN Sriwedari 01. Keywords: Pretest Method; learning outcomes Abstrak: Keefektifan Metode Pretest Berbantu Google Form Terhadap Hasil Belajar Peserta Didik Tema Selalu Berhemat Energi Kelas IV SDN Sriwedari 01. Penelitian ini dilakukan karena rendahnya hasil belajar peserta didik kelas IV sekolah dasar pada pembelajaran di masa pandemi Covid-19. Sedangkan rendahnya hasil belajar peserta didik, disebabkan oleh rendahnya hasil belajar tersebut adalah kurangnya pembelajaran yang efektif dalam mengoptimalkan hasil belajar peserta didik kelas IV pada masa pandemi Covid-19. Oleh karena itu, penelitian ini bertujuan untuk mengetahui keefektifan metode pretest berbantu Google Form terhadap hasil belajar peserta didik tema Selalu Berhemat Energi kelas IV SDN Sriwedari 01. Penelitian ini juga dilakukan dengan menggunakan metode penelitian kuantitatif dengan jenis penelitian true eksperimental design dan bentuk rancangan static group comparison design. Populasi yang digunakan yaitu peserta didik kelas IV SDN Sukorukun sebagai kelas kontrol dan peserta didik kelas IV SDN Sriwedari 01 di Kabupaten Pati sebagai kelas eksperimen tahun pelajaran 2020/2021, dengan jumlah sampel yaitu sebanyak 37 peserta didik yang terdiri dari 21 peserta didik kelas kontrol dan 16 peserta didik kelas eksperimen yang menggunakan teknik nonprobably sampling. Adapun data yang diambil dalam penelitian ini yaitu melalui wawancara, kuesioner/tes, dokumentasi, dan observasi. Hasil belajar peserta didik dari data kuesioner/tes menunjukkan bahwa persentase ketuntasan klasikal kelas eksperimen (68,75%) lebih kecil dari persentase ketuntasan klasikal kelas kontrol (90,48%) dengan nilai KKM kelas kontrol dan kelas eksperimen yaitu 65. Sedangkan pada analisis uji-t, diperoleh thitung = 0,55 dan ttabel = 2,08 sehingga diperoleh thitung< ttabel dengan selisih persentase ketuntasan klasikal peserta didik yang tuntas KKM sebesar 21,73%. Sehingga metode pretest berbantu Google Form tidak efektif terhadap hasil belajar peserta didik tema Selalu Berhemat Energi kelas IV SDN Sriwedari 01. Kata Kunci: Metode Pretest;hasil belajar